Architectural Interior Modeling Product Design Based on the Multimedia Three-Dimensional Hybrid Algorithm - Tao Su; Gang Ouyang (Advances in Multimedia)
With the continuous development of social economy, people’s aspiration for architecture is getting higher and higher. Designing more functional and aesthetically pleasing interior styling products is increasingly important research. Relying on the multimedia three-dimensional hybrid algorithm, the mathematical modeling of the relationship between visual comfort and chromaticity is modeled in this paper, to construct an economical and practical interior architectural design model that takes into account color comfort perception, that is, complete “design, conversion, editing and repair, and semantic and coordinate supplement” and other chain construction to realize usable interior architectural design models. The simulation experiment results show that the model based on the multimedia 3D hybrid algorithm has high practicability.